Nanotechnology in Civil Infrastructure A Paradigm Shift - Gopalakrishnan, Kasthurirangan.; Gopalakrishnan, Kasthurirangan.; Birgisson, Bjorn.; Birgisson, Bjorn.; Taylor, Peter.; Taylor, Peter.; Attoh-Okine, Nii O.; Attoh-Okine, Nii O. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Nanotechnology in Civil Infrastructure is a state-of-the art reference source describing the latest developments in nano-engineering and nano-modification of construction materials to improve the bulk properties, development of sustainable, intelligent, and smart concrete materials through the integration of nanotechnology based self-sensing and self-powered materials and cyber infrastructure technologies, review of nanotechnology applications in pavement engineering, development of novel, cost-effective, high-performance and long-lasting concrete products and processes through nanotechnology-based innovative processing of cement and cement paste, and advanced nanoscience modeling, visualization, and measurement systems for characterizing and testing civil infrastructure materials at the nano-scale. Researchers, practitioners, undergraduate and graduate students engaged in nanotechnology related research will find this book very useful. .